Developing a blind robot: Study on 2D Mapping - Lee Siau, Yin; Yeoh Kai, Sheng; Aryuanto, Soetedjo (2008)
This paper is about developing a blind robot which focuses on the study of continuous and discrete 2D mapping. Ultrasonic sensors are used to sense the obstacles while the robot is moving. User is also allowed to vary the speed of robot and move forward and backward with the robot. There is a two-dimensional memory map program to track the robot position and obstacles detected by proximity sensor on the robot. The program written is able to control the robot by displaying the two-dimensional map that plots the location of the robot and obstacles, displaying coordinates of the robot, control turning of robot at various degrees and move or stop the robot.